COMMUNICATION AND EMOTIONAL SKILLS DEVELOPMENT PROGRAM FOR CHILDREN IN ORPHANAGES - Alisya Mutia Mantika; Rima Tamara Aldisa (Adisam Publisher, 2024)
Through a series of structured activities and based on child center learning principles, this program aims to strengthen the ability to convey their ideas, feelings and needs effectively, help children understand and manage their emotions healthily, improve communication and interaction skills positively with other people, as well as building healthy and harmonious relationships with the surrounding environment. With a focus on developing interpersonal skills, problem solving, and self-understanding, this program will help in building positive relationships with others and improve the quality of their social interactions. Thus, it is hoped that the implementation of this program will have a positive impact on social, emotional and psychological development of children in orphanages, well provide strong foundation for their personal growth and future success.